Materials challenges and testing for manufacturing, mobility, biomedical applications and climate - Bollinghaus, Thomas; Manonukul, Anchalee; Lexow, Jürgen; Udomkichdecha, Werasak (Springer International Publishing, 2014)
In four parts, the book focuses on materials science developments in the area of 1) Reliable manufacturing with advanced Materials 2) Material challenges for mobility systems 3) Materials challenges for biomedical applications 4) Material challenges in mitigation and adaptation to climate change   This book presents selected contributions of exceptional young postdoctoral scientists to the 4th WMRIF Workshop for Young Scientists, hosted by the National Metal and Materials Technology Center (MTEC), in Pathum Thani, Thailand, August 28 - 31, 2012.